A RAB27A duplication in several cases of Griscelli syndrome type 2: An explanation for cases lacking a genetic diagnosis. Issue 10 (19th June 2017) - Grandin, Virginie; Sepulveda, Fernando E; Lambert, Nathalie; Al Zahrani, Mofareh; Al Idrissi, Eman; Al‐Mousa, Hamoud; Almanjomi, Fahd; Al‐Ghonaium, Abdulaziz; K. Habazi, Murad; A. Alghamdi, Hamza; Picard, Capucine; Bole‐Feysot, Christine; et al.
Abstract : Griscelli syndrome results from loss of function mutations in RAB27A that impair lymphocyte cytotoxicity leading to severe immune dysregulation. Several cases in Saudi Arabia lack genetic diagnosis. In 7 families, combination of linkage analysis, CNV score and careful inspection of targeted NGS data evidenced a common tandem duplication of exon 2–5 of RAB27A, inserted within the first RAB27A copy, resulting in a premature stop codon with functional consequences on cytotoxicity. A microhomology‐mediated mechanism of the duplication is favored. Abstract: Griscelli syndrome type 2 (GS2) is a rare and often fatal autosomal recessive, hyperinflammatory disorder. It is associated with hypopigmentation of the skin and the hair, resulting in the characteristic pigment accumulation and clumping in the hair shaft. Loss‐of‐function mutations in RAB27A, resulting from point mutations, short indel, or large deletions, account for all the cases reported to date. However, several GS2 cases originating from Saudi Arabia lack a genetic diagnosis. Here, we report on a new RAB27A genetic anomaly observed in seven Saudi Arabia families that had remained negative after extensive molecular genomic DNA testing. Linkage analysis and targeted sequencing of the RAB27A genomic region in several of these patients led to the identification of a common homozygous tandem duplication of 38 kb affecting exon 2–5 and resulting in a premature stop codon. The pathogenic effect of this duplication was confirmed by a cDNA analysis and functional assays. The identification of microhomology flanking the breakpoint site suggests a possible underlying mechanism.